The Influence of Leadership, Motivation, and Discipline on The Consistency of Employee Performance Levels (Case Study at The General Bureau of The Ministry of State Secretariat Republic of Indonesia) - Supriyatin; Zainal Rahman (MJK PUBLISHER, 2025)
This research aims to determine the influence of leadership through consistency on performance, to determine the influence of motivation through consistency on performance, to determine the influence of discipline through consistency on performance. This research method uses questionnaires and observation methods, the type of data used is quantitative data, the data source used is primary data. The population in this study were employees at the General Bureau of the Ministry of State Secretariat of the Republic of Indonesia. The number of samples was 119. Data collected from the questionnaire was processed using the SPSS version 30 application. The results of this research conclude that there is a significant influence on each independent variable (Leadership, Motivation, Discipline) through intervening (Consistency) on the dependent variable (Performance).